2023
DOI: 10.4081/jphia.2023.2516
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of pinostrobin propionate and pinostrobin butyrate: Cytotoxic activity against breast cancer cell T47D and its selectivity index

Abstract: Backgrounds: Pinostrobin has the potential activity as an anti-cancer. However, its activity is still lower than the anticancer drugs on the market. To increase its activity, pinostrobin derivatives have been synthesized, namely pinostrobin propionate and pinostrobin butyrate, which are predicted to have better activity and lower toxicity than pinostrobin after being tested by in silico approach. So the compound deserves to be tested for its anticancer activity and selectivity on normal cells. Objective: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Siswandono et al () have researched the analgesic effect on 5-O-Acylpinostrobin derivatives by molecular modelling, synthesis and Quantitative Structure-Activity Relationship (QSAR), and the study's finding yielded four derivative compounds, including pinostrobin acetate, pinostrobin propionate, pinostrobin butyrate, and pinostrobin pentanoate (Siswandono et al, 2020). Two of its derivative compounds, pinostrobin propionate and pinostrobin butyrate were examined in T47D breast cancer cells for their cytotoxic efficacy and selectivity against breast cancer (Widiandani et al, 2023). The result revealed that both derivatives showed greater activity and selectivity than pinostrobin, so these compounds are promising to be further developed as anticancer candidates (Widiandani et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Siswandono et al () have researched the analgesic effect on 5-O-Acylpinostrobin derivatives by molecular modelling, synthesis and Quantitative Structure-Activity Relationship (QSAR), and the study's finding yielded four derivative compounds, including pinostrobin acetate, pinostrobin propionate, pinostrobin butyrate, and pinostrobin pentanoate (Siswandono et al, 2020). Two of its derivative compounds, pinostrobin propionate and pinostrobin butyrate were examined in T47D breast cancer cells for their cytotoxic efficacy and selectivity against breast cancer (Widiandani et al, 2023). The result revealed that both derivatives showed greater activity and selectivity than pinostrobin, so these compounds are promising to be further developed as anticancer candidates (Widiandani et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Two of its derivative compounds, pinostrobin propionate and pinostrobin butyrate were examined in T47D breast cancer cells for their cytotoxic efficacy and selectivity against breast cancer (Widiandani et al, 2023). The result revealed that both derivatives showed greater activity and selectivity than pinostrobin, so these compounds are promising to be further developed as anticancer candidates (Widiandani et al, 2023). Therefore, pinostrobin and other derivatives can be predicted to have potential as anti-breast cancer agents.…”
Section: Introductionmentioning
confidence: 99%